So long! : Walt Whitman's poetry of death - Aspiz, Harold, 1921- (Book collections on Project MUSE., 2004)
Through a close reading of Leaves of Grass, its constituent poems, particularly Song of Myself and Whitman's prose and letters, Aspiz charts how the poet's exuberant celebration of life is a consequence of his central concern: the ever presence of death and the prospect of an afterlife.